Outcomes of permanent canines on the cleft side after secondary alveolar grafting using different materials in complete unilateral cleft lip and palate - Bruno Mariano Ribeiro Braga; Claudia Resende Leal; Roberta Martinelli Carvalho; Gisele da Silva Dalben; Terumi Okada Ozawa (University of São Paulo, 2023)
Abstract The prevalence of impaction of the permanent canine on the cleft side (PCCS) ranges from 12-35% after alveolar bone grafting (ABG). PCCSs usually develop above other permanent teeth in the alveolar process, gradually becoming vertical until they reach the occlusal plane. The type of cleft, hypodontia of lateral incisor on the cleft side, slower PCCS root development, and genetic factors are predictors of impaction and/or its ectopic eruption. Objective: To compare the behavior of PCCS in individuals with complete unilateral cleft lip and palate (UCLP) subjected to secondary alveolar grafting (SAG) with different materials. Methodology: This retrospective longitudinal study analyzed 120 individuals undergoing SAG with iliac crest bone, rhBMP-2, and mandibular symphysis. The individuals were selected at a single center and equally divided into three groups. Panoramic radiographs were analyzed by the Dolphin Imaging 11.95 software to measure PCCS angulation and PCCS height from the occlusal plane at two different timepoints. Results: No statistical significance was found between grafting materials (P=0.416). At T1, the PCCS height from the occlusal plane was greater for rhBMP-2 and mandibular symphysis compared to iliac crest bone. The lateral incisor on the cleft side was not related to success or lack of eruption of PCCS (P=0.870). Conclusion: Impaction rates of PCCS were similar for the materials studied. Absence of the lateral incisor on the cleft side did not prevent spontaneous eruption of PCCSs.